The relationship between accessibility of urban and rural high schools and enrollment rate: A county-level study - Xinlong Li; Sharifah Salwa Syed Mahdzar; Khairul Anwar Mohamed Khaidzir; Iziq Eafifi Ismail (PLoS ONE, 2025)
The study investigates the relationship between high school accessibility and enrollment rates in urban and rural areas within a county. The main goal is to explore how spatial accessibility to high schools impacts student enrollment opportunities, particularly in the context of urban-rural disparities. Using empirical analysis, the study evaluates the effects of transportation infrastructure, school distribution, and government policies on educational access and fairness. The findings reveal, there is no significant correlation between high school accessibility and enrollment rates in both urban and rural areas. Furthermore, the research shows that improvements in rural infrastructure and policies have helped mitigate potential disparities, leading to a more balanced educational landscape. This study provides a theoretical framework for assessing high school accessibility and its impact on enrollment rates, offering valuable insights for policy makers looking to optimize educational resources and promote fairness. The findings highlight the need for further research with larger samples and the inclusion of additional variables to understand the broader impact of accessibility on education.